Marketplace Acceptance and E-WOM on the Decision to Use the Zalora Application: Penerimaan Marketplace dan E-WOM pada Keputusan Penggunaan Aplikasi Zalora - Al-Hafidz, Thariq Naufaldy; Rochmaniah, Ainur (House of Wisdom: Journal on Library and Information Sciences, 2025)
General Background: The rapid development of technology has facilitated the growth of e-commerce, transforming traditional in-person transactions into online activities. Specific Background: This shift has been particularly massive in Indonesia, with the number of e-commerce users surging during the COVID-19 pandemic. As a prominent player in the fashion and beauty e-commerce sector, Zalora has become a popular platform, attracting significant visitor traffic. Knowledge Gap: To better understand consumer behavior within this context, this research addresses a gap in the literature by examining the specific factors influencing the decision to use the Zalora application. Aims: This study aims to analyze the effect of Marketplace Acceptance and Electronic Word of Mouth (E-WOM) on the decision to use the Zalora application. Results: Using a quantitative method with data from 90 respondents, the study found a strong correlation, with a coefficient value of 0.901. The adjusted R-squared value of 0.808 indicates that Marketplace Acceptance and E-WOM collectively explain 80.8% of the variability in the decision to use the application. Novelty: This research provides new insights into the specific relationship between these variables and consumer decisions regarding the Zalora application, supporting and, in some cases, refuting previous findings. Implications: The findings suggest that both Marketplace Acceptance and E-WOM have a significant positive influence, either partially or simultaneously, on a consumer's decision to use the Zalora application. Highlights :  Zalora Application: This exploratory study examines how Marketplace Acceptance and E-WOM affect the decision to use the Zalora application. Quantitative Method: The research uses a quantitative method, gathering data through online questionnaires from 90 respondents. Significant Influence: The study found a very strong correlation between the variables, with Marketplace Acceptance and E-WOM explaining 80.8% of the variability in the decision to use the Zalora app. Keywords : Decision to Use, E-WOM, Marketplace Acceptance, Quantitative, Zalora